Contesting Strategic Narratives in a Global Context: The World Watches the 2016 U.S. Election. (January 2019) - Kluver, Randolph; Cooley, Skye; Hinck, Robert
National media narratives often embody "strategic narratives" that embody national consensus on geopolitics. The 2016 U.S. presidential election was an event of intense international interest, both for its internal drama, but also for the policy positions of both of the major candidates. This paper presents a comparative analysis of how media in four key regions covered the U.S. presidential election and its immediate aftermath. Researchers utilized an innovative technology that allowed the teams to harvest media content, from almost seventy-five global news sources, in Arabic, Farsi, Chinese, and Russian. This paper utilized the theoretical construct of strategic narratives to demonstrate how the U.S. election is incorporated into narrative constructions of global order. Theoretically, this project seeks to deepen our understanding, from a comparative methodology, of how "events, " such as the U.S. presidential election, provide the raw material for global contestations of the global order. The essay also provides a mechanism for analyzing and evaluating these narratives using Fisher's narrative paradigm. Finally, the paper demonstrates an innovative methodological approach to comparative analysis from disparate cultural and news traditions, languages, and patterns of access to media.